Perbandingan Hukum Usaha Jasa Titip: Perspektif Hukum Bisnis Indonesia dan Thailand - Devi Panggabean, Azra Sri; Sumiati Bondar, Lista Ade; Tampubolon, Putri Melani; Silalahi, Jonathan Agung; Anggusti, Martono (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2024)
This study aims to analyze and compare the legal regulations governing consignment services between Indonesia and Thailand, particularly regarding licensing, consumer protection, and taxation. This research employs a normative juridical approach with a descriptive analytical method, utilizing primary data from the legal regulations of both countries, such as Law No. 8 of 1999 on Consumer Protection in Indonesia and the Consumer Protection Act B.E. 2522 (1979) in Thailand, as well as secondary data from legal literature. The findings reveal that consignment service regulations in Indonesia are still minimal and fragmented, leading to legal uncertainty for business actors and consumers. In contrast, Thailand has more structured regulations that support consignment services in terms of business licensing and consumer protection. This study highlights the need for regulatory improvements in Indonesia to create a more conducive and harmonious business climate.